Observações de micorriza vesicular-arbuscular em diferentes espécies de plantas - Caldeira, Sidney Fernando; Martins Chaves, Geraldo; Zambolim, Laércio (Revista Ceres, 2025)
This work describes the occurrence of vesicular-arbuscular mycorrhizal fungi on coffee (Coffea arabica), soybean (Clicyne max), lemon (Citrus iimonea) and Guinea grass (Melinnis minutiflora), growing at three different localities near Vigosa, Minas Gerais. The pH of the soil samples ranged from 4,5 to 5,9. The spores of the vesicular-arbuscular mycorrhizal fungi were collected by using the wet sieving and decating method and a sucrose density gradient column. The roots were stained with lactophenol cotton blue, after treatment with 10% KOH. The mycorrhizal fungi found were: Acaulospora trappei, A. scrobiculata. A. sp., Glomus macrocarpus, G. etunicatus, G. ocultus, G. fecundisporus, G. fasciculatus and Gigaspora margarita. The Acaulospora species were predominant in almost all samples collected. This paper records, for the fist time, several species of vesicular-arbuscular mycorrhizal fungi on coffee and Guinea grass. The percentage of root infection by the mycorrhizal fungi varied with plant species, and was not influenced by the level of phosphorus in the soil.